Impact of depth and extent of lymphovascular space invasion on lymph node metastasis and recurrence patterns in endometrial cancer. Issue 6 (22nd September 2015) - Matsuo, Koji; Garcia‐Sayre, Jocelyn; Medeiros, Fabiola; Casabar, Jennifer K.; Machida, Hiroko; Moeini, Aida; Roman, Lynda D.
<x xml:space="preserve">Abstract</x> Background and Objectives To determine the significance of depth and extent of lymphovascular space invasion (LVSI) on lymph node metastasis and recurrence in endometrial cancer. Methods A case‐control study was conducted to examine LVSI‐positive (n = 70) and LVSI‐negative (n = 641) stage I–III endometrial cancer cases that underwent hysterectomy‐based surgical staging. The risk of lymph node metastasis and distant recurrence was estimated based on LVSI patterns. Results In multivariate analysis, deep (>50% invasion), and extensive (≥7 foci/slide) LVSI patterns had a significantly increased risk of lymph node metastasis (incidence 57.6% and 72.7%, odds ratio 33.8 and 49.9, respectively, P < 0.001) as compared to other traditional uterine factors (>50% myometrial tumor invasion, cervical stromal invasion, and adnexal involvement: incidence range 30.4–37.9%, odds ratio range 3.80–7.03). Deep and extensive of LVSI patterns were both significantly correlated to distant recurrence (P < 0.001). Among women who received postoperative chemotherapy, deep and extensive LVSI patterns did not have increased risks for distant recurrence compared to no LVSI (P = 0.47 and 0.32, respectively). Among women who received postoperative radiotherapy, the depth of LVSI was significantly associated with recurrence outside the radiated field (P = 0.02). Conclusions Depth and extent of LVSI are important predictors for lymph node metastasis and distant recurrence in endometrial cancer. J. Surg. Oncol. 2015;112:669–676. © 2015 Wiley Periodicals, Inc.